Abdominal Pain as First Manifestation of New Coronavirus Infection COVID-19 - M. R. Skhirtladze; A. A. Timofeeva; E. L. Bueverova; M. N. Aladin; R. T. Rzayev (Российский журнал гастроэнтерологии, гепатологии, колопроктологии)
Aim. A clinical case description of abdominal pain as the ﬁrst manifestation of the new coronavirus infection COVID-19. Key points. A 80-yo patient was admitted to a surgical unit with growing epigastric pain and fever. Acute abdomen was diagnosed negative, chest computed tomography (CT) revealed two-sided ground-glass opacity, discharged. Hospitalised in a severe condition with presumed new coronavirus infection at the Vasilenko Clinic of Internal Disease Propaedeutics, Gastroenterology and Hepatology, the Sechenov University. COVID-19 agent RNA was detected with PCR. Diagnosis: new coronavirus infection COVID-19, severe degree, community-acquired bilateral polysegmental pneumonia, severe degree, respiratory failure type 1. Therapy with azithromycin, hydroxychloroquine, enoxaparin subcutaneously. Respiratory distress increased on day 7 at the clinic, with 50–75% lesion in chest CT, which required ordering of dexamethasone intravenously, with a subsequent dose reduction and withdrawal, and levoﬂoxacin. Upon the treatment, abdominal pain was eliminated, body temperature normalised and the volume of aﬀected parenchyma decreased. The patient was discharged for outpatient care. Patients with SARS-CoV-2 may have abdominal complaints that may require exclusion of an acute surgical pathology. These circumstances inevitably waste time of assisting patients suﬀering the new coronavirus infection and worsen the prognosis due to severe pneumonia.Conclusion. A gastroenterological debut of the new coronavirus infection with the main symptoms of abdominal pain has been presented. The currently continued unfavourable epidemiological situation demands diagnosis for SARSCoV-2 and COVID-19-associated pneumonia upon the exclusion of peritoneal symptoms even in absence of respiratory complaints.